Cu(OTf)2/TBHP/O2-Mediated Tandem Oxidative Reaction: Easy Access to Benzopyrano[4,3-b]pyridines - Cheng, Dongping; Yang, Hongjiao; Xia, Hongshuang; Gu, Huafang; Li, Jing-Hua; Xu, Xiaoliang (Synthesis, 2023)
An effective tandem reaction of 4-aminocoumarins and 1,3-diarylpropenes mediated by Cu(OTf)2/TBHP (tert-butyl hydroperoxide)/O2 that provides various benzopyrano[4,3-b]pyridines in moderate to good yields is disclosed. The reaction proceeds through oxidative coupling, intramolecular cyclization, and dehydro-aromatization. This approach has the advantages of high atom-economy, environmental compatibility, and wide substrate scope.
Keywords: tandem reaction; oxidative coupling; TBHP; 4-aminocoumarin; benzopyrano[4,3-b]pyridines